Assessment of Adoption Gaps in Gobhi Sarson (Brassica Napus L.) Production Technologies in Amritsar and Tarntaran Districts of Punjab - S S Walia , Rajni , Satpal Singh , C S Aulakh and R S Gill, (Indian Journal of Extension Education, 2013)
The present study was undertaken in Amritsar and Tarntaran districts of Punjab to analyze the status of gobhi sarsonproduction technology, constraints in its cultivation and the possibilities of increasing production. Afundamental problemto overcome insignificantly increasing oilseed production is to change the prevailing perceptions of their status as asubsistence crop and to consider as a commercial crop. This will require aggressive on-farm demonstration of the viabletechnical options, to alleviate the gaps in technology of production of oilseed crops. It emphasizes dissemination ofimproved varieties and low-cost, environmental friendly crop husbandry techniques. Keeping this in view, front linedemonstrations (FLDs) on gobhi sarson, existing technology v/s recommended technology were conducted during rabi2010-11 and 2011-12 and have proved immensely useful in increasing the production and productivity of oilseed crops inthe districts alongwith evaluation of adoption gaps. The improved practice produced 9.6 and 13.4 per cent more seed yieldand 14.8 and 19.8 per cent higher net returns of gobhi sarson than the crop raised by farmers themselves in 2010-11 and2011-12, respectively